The development path less traveled : the experience of Rwanda - Redifer, Laure (Washington, D.C International Monetary Fund (IMF), 2020)
This paper explores some of the key factors behind Rwanda key successes, including unique institution-building that emphasized governance and ownership; aid-fueled and government-led strategic investment in people, infrastructure, and high-yield economic activity; re-establishment and expansion of a domestic tax base; policies to reduce aid dependency by attracting private investment and bolstering exports; and a purposeful strategy to harness the economic power of gender inclusion (IMF page)​
Foreword -- Acknowledgments -- Executive Summary Introduction -- 1. Overview of Rwanda’s Growth Performance and Its Use of International Support -- 2. Purposeful Policy and Institution Building -- 3. Public Investment and Structual Transformation -- 4. Raising Domestic Resources -- 5. Transitioning from Development Assistance to Trade and Investment -- 6. Gender Inclusion to Promote Growth -- 7. Conclusion and Future Financing for Development
Includes bibliographical references (pages 91-99)
Keywords: Economic development; ECONOMIC DEVELOPMENT; SUSTAINABLE DEVELOPMENT; ECONOMIC CONDITIONS; ECONOMIC HISTORY; RWANDA